Diagnostic performance of MRI for assessment of response to neoadjuvant chemoradiotherapy in oesophageal cancer. Issue 5 (25th February 2019) - Vollenbrock, S E; Voncken, F E M; van Dieren, J M; Lambregts, D M J; Maas, M; Meijer, G J; Goense, L; Mook, S; Hartemink, K J; Snaebjornsson, P; ter Beek, L C; Verheij, M; et al.
Abstract: Background: Patients with a pathological complete response (pCR) after neoadjuvant chemoradiotherapy (nCRT) for oesophageal cancer may benefit from non-surgical management. The aim of this study was to determine the diagnostic performance of visual response assessment of the primary tumour after nCRT on T2-weighted (T2W) and diffusion-weighted (DW) MRI. Methods: Patients with locally advanced oesophageal cancer who underwent T2W- and DW-MRI (1·5 T) before and after nCRT in two hospitals, between July 2013 and September 2017, were included in this prospective study. Three radiologists evaluated T2W images retrospectively using a five-point score for the assessment of residual tumour in a blinded manner and immediately rescored after adding DW-MRI. Histopathology of the resection specimen was used as the reference standard; ypT0 represented a pCR. Sensitivity, specificity, area under the receiver operating characteristic (ROC) curve (AUC) and interobserver agreement were calculated. Results: Twelve of 51 patients (24 per cent) had a pCR. The sensitivity and specificity of T2W-MRI for detection of residual tumour ranged from 90 to 100 and 8 to 25 per cent respectively. Respective values for T2W + DW-MRI were 90–97 and 42–50 per cent. AUCs for the three readers were 0·65, 0·66 and 0·68 on T2W-MRI, and 0·71, 0·70 and 0·70 on T2W + DW-MRI ( P = 0·441, P = 0·611 and P = 0·828 for readers 1, 2 and 3 respectively). The κ value for interobserver agreement improved from 0·24–0·55 on T2W-MRI to 0·55–0·71 with DW-MRI. Conclusion: Preoperative assessment of residual tumour on MRI after nCRT for oesophageal cancer is feasible with high sensitivity, reflecting a low chance of missing residual tumour. However, the specificity was low; this results in overstaging of complete responders as having residual tumour and, consequently, overtreatment. Graphical Abstract: Treatment of locally advanced oesophageal cancer consists of neoadjuvant chemoradiotherapy (nCRT) followed by surgery. In 25–30 per cent of these patients, the resection specimen shows a pathological complete response. This study shows that preoperative response assessment after nCRT performed visually on (diffusion-weighted) MRI has promising overall diagnostic performance. To further increase the accuracy of response assessment, larger studies are needed, ideally using a multimodal approach combining (diffusion-weighted) MRI with endoscopy/endoscopic ultrasonography and fluorodeoxyglucose PET/CT. T2W, T2-weighted; DW, diffusion weighted. Not there yet